Clinical Outcome and Echocardiographic Evaluation of Inferior Myocardial Infarction with Right Ventricular Involvement - Guha, B; Majumder, AAS; Chowdhury, MNA; Hossain, MM; Mandal, AK (Cardiovascular Journal, 2012)
Background : Acute right ventricular myocardial infarction complicates inferior wall myocardial infarction with an incidence of 14-84%. ECG is the cornerstone in initial diagnosis as it is cost effective and done easily. Echocardiographic analysis of the right ventricular involvement can shed light on the severity of the disease. Hence we aimed to study right ventricular infarction in acute inferior wall myocardial infarction using right precordial lead as well as echocardiography. Methods: Present study is based on the analysis of 100 patients admitted to Coronary care unit of the National Institute of Cardiovascular Diseases & Hospital during July 2010 to June 2011, with acute inferior wall myocardial infarction. 12 lead ECG with thorough physical examination was done along with right precordial mapping. ST ³ 1mm in V4R was initial diagnostic of right ventricular involvement followed by echocardiographic assessment of RV and LV within 24 hours. Results: A total of 50 patients showed right ventricular involvement with V4R being the sensitive lead. Echocardiography showed mean RVEF of patients with 29.5 % ± 9.5 in comparison of 44.9%±12.2 without right ventricular involvement. Right ventricular involvement presented with bradycardia (40%) and hypotension, 80% Kussmauls sign, 14% with complete heart block. Mortality in right ventricular involvement was 6 times higher than without right ventricular involvement (12 %). Conclusion: Clinical signs and symptomatology are not fully diagnostic of RVI in inferior wall acute MI. ECG can diagnose (using right precordial mapping) this condition very early. Echocardiography help to assess the right ventricular function high-risk groups for aggressive management like primary PCI. Early diagnosis will help in careful monitoring and management of such cases. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10457 Cardiovasc. j. 2012; 4(2): 132-138